Efficient synthesis of 6-nitro-1,2,3,4-tetrahydroquinoline: an experimental and theoretical study of regioselective nitration - ROZAS, ISABEL (My University, 2011)
A revision of the literature on the nitration of tetrahydroquinolines yielded a number of inconsistencies. Thus, we have carried out a thorough study on the nitration of tetrahydroquinoline and some of its N-protected derivatives both experimentally and at theoretical level. The favoured position for nitration of tetrahydroquinoline depends on the protonation state of the ring amine group. In general, nitration is carried out in acidic conditions and, thus, tetrahydroquinoline would be N-protonated. However, if the tetrahydroquinoline amino group is protected, the neutral system will be the one undergoing nitration. Different protecting groups were explored varying, not only electronic and steric effects, but also deprotection conditions. Additionally, different reaction reagents and conditions were investigated. From this study we were able to achieve total regioselectivity for nitration at the 6-position. A very detailed NMR study was required to unequivocally characterise the four nitro isomers and, hence, mono and bi-dimensional 1H and 13C NMR studies were carried out. In parallel, a computational study has been performed that is in agreement with the experimental results obtained. With this purpose, all the ?-complexes of the four nitro isomers neutral and N-protonated were optimized both in gas phase and in water condensed phase by using the B3LYP/6-31++G** level of computation.
PUBLISHED
Keywords: tetrahydroquinoline